2018
DOI: 10.1038/s41598-018-33198-0
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Mechanisms on High Retention Annealed MgO-based Resistive Switching Memory Devices

Abstract: We report on the conduction mechanisms of novel Ru/MgO/Cu and Ru/MgO/Ta resistive switching memory (RSM) devices. Current-voltage (I–V) measurements revealed Schottky emission (SE) as the dominant conduction mechanism in the high resistance state (HRS), which was validated by varying temperatures and transmission electron microscopy (TEM) results. Retention of more than 10 years at 85 °C was obtained for both Ru/MgO/Ta and Ru/MgO/Cu RSM devices. In addition, annealing processes greatly improved the consistency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The electrical conduction of the Ag/(PEA) 2 Cs 3 Pb 4 I 13 /Pt memory device differed in the HRS and LRS during the SET operation under a voltage sweep of 0 V → +0.8 V → 0 V. First, it was found that the ohmic conduction plot had a slope of 0.99, with a linear relation of ln I vs. ln V in the LRS region after the abrupt current increase 23,[52][53][54] . In the HRS region, the relation of ln I vs. ln V was nonlinear with a slope of 0.26, which verifies that Schottky emission is dominant 23,53,55 . To better understand the two types of electrical conduction mechanisms, i.e., ohmic conduction in the LRS and Schottky emission in the HRS, the I-V curves of each resistance state were replotted with linear fitting lines.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The electrical conduction of the Ag/(PEA) 2 Cs 3 Pb 4 I 13 /Pt memory device differed in the HRS and LRS during the SET operation under a voltage sweep of 0 V → +0.8 V → 0 V. First, it was found that the ohmic conduction plot had a slope of 0.99, with a linear relation of ln I vs. ln V in the LRS region after the abrupt current increase 23,[52][53][54] . In the HRS region, the relation of ln I vs. ln V was nonlinear with a slope of 0.26, which verifies that Schottky emission is dominant 23,53,55 . To better understand the two types of electrical conduction mechanisms, i.e., ohmic conduction in the LRS and Schottky emission in the HRS, the I-V curves of each resistance state were replotted with linear fitting lines.…”
Section: Resultsmentioning
confidence: 60%
“…To further clarify whether Schottky emission is dominant in the HRS region during the SET operation, the nonlinear I-V curve of the HRS was replotted as ln I vs. the square root of the applied voltage (ln I ∝ V 1/2 ), as illustrated in Fig. 5c 52,55,56 . The fitting result shows a linear relationship of ln I ∝ V 1/2 , which can be taken as evidence that Schottky emission is dominant in the HRS region, according to the following equation: 23 ln…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, Schottky emission also occurs because of thermal activation. When the positive bias is applied to the top Ag electrode, thermally activated electrons receive a sufficient amount of energy to jump from the valence band to the conduction band [30][31][32]. Therefore, it can be concluded that different material devices with diverse geometry and parameters can provide an outcome of conducting filament occurrence conditional to the ion migration rate and redox reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Resistive switching is observed in MgO based structures [ 55 , 56 ]. Ferromagnetism combining with multilevel switching characteristics is also reported in MgO capacitor [ 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%